A Historiographical Overview Families of the Kingdom of Guatemala - González Galeotti, Francisco Rodolfo (2021)
This paper is a general review of academic production that addresses or takes into account the history of the family in the kingdom of Guatemala and the first independent years of Central America and Chiapas. A general review is carried out on the main historiographic findings published and presented between 1978 and 2020. The analysis has been broken down into several categories that allow a panoramic view of the analyzed studies. Subsequently, the main lines of research carried out to date were outlined. Finally, lines of work are proposed that can be explored in the future by young researchers on the subject.